Readiness of Specialists in the Field of Education for Social Partnership: Inclusive Aspect - Chupakhina, Svitlana; Skomorovska, Iryna; Kyrsta, Nataliia; Krul, Larysa (Journal of Vasyl Stefanyk Precarpathian National University, 2022)
The article deals with the problem of the main aspects of the readiness of education professionals for social partnership for the development of inclusive processes. The authors aimed at substantiating and exploring the main aspects of the social partnership of family and educational institution for the development of inclusion and revealing the features of the formation of readiness of teachers and parents for this process. It is established that the organization of systematic and scientifically-based and practice-oriented work, which is aimed at forming parents' ideas and skills in the field of family education, is important for improving parental competence. The principal features of the partnership are highlighted: the long-term nature of the interaction and mutual responsibility. It is determined that social partnership is an educational interaction between teachers and parents, which is characterized by a common attitude and coordination of actions aimed at the development of children and taking into account their individual characteristics and capabilities. The goal of the social partnership is to improve the quality of education for children with special needs in an inclusive space, which will be effective if all participants are coordinated, pool their resources and personal interests in developing competencies needed to make decisions about child development. It is proved that the implementation by teachers and parents of children with special needs of individual educational trajectories on the basis of partnership ensures the transition of participants in the educational process to a higher level of competence development in a favorable inclusive environment.